Financial liberalization and the economic crisis in Asia - Lee, Chung H. (European Institute of Japanese Studies East Asian economics and business studies series, 2003)
Financial Liberalization and the Economic Crisis in Asia analyses how financial liberalization was undertaken in eight Asian countries and how it might be linked to the subsequent crises.